Financial and non-financial benefits of carbon controls. Issue 2 (20th July 2020) - Bui, Binh; Truong, Thu Phuong; Chapple, Ellie J.
Abstract : Purpose: This study aims to understand the organisational benefits of carbon-focussed management control systems (carbon MCS) under a regulatory context. Design/methodology/approach: The authors conduct a survey of 85 New Zealand (NZ) organisations covering different industries, sizes and compliance obligations. Findings: The results suggest a significant direct positive impact of carbon MCS on organisations' non-financial benefits and an indirect impact on financial benefits via non-financial benefits. The impact on non-financial benefits is strongest when a whole carbon MCS package is used rather than individual carbon controls. However, the highest impact on financial benefits are attained when only diagnostic controls are used rather than other controls or the whole MCS package. Firms in primary, manufacturing and energy sectors and those with export activities are less likely to achieve organisational benefits, while those with a compliance obligation under the emissions trading scheme are more likely to perceive such benefits. Research limitations/implications: The study has a limited sample size (85 firms), a unique context (NZ) and coves only large firms. Further, there are no objective performance measures to validate survey responses regarding organisational benefits. Practical implications: The findings provide a business case for managers and practitioners in formulating their strategic and MCS responses to climate change issues. Originality/value: The authors focus on carbon MCS and adopt a wider range of carbon MCS levers than previous research. The authors discern not only non-financial benefits but also financial benefits from MCS use.